Bridging intracellular scales by mechanistic computational models. (August 2018) - Widmer, Lukas Andreas; Stelling, Jörg
Graphical abstract: Highlights: Intracellular dynamics span many spatial, temporal, and molecular abundance scales. Multi-class models enable to bridge scales while being computationally tractable. Recent advances on simulation methods allowed for various application studies. Active transport, dynamic geometries, and inference pose substantial challenges. Abstract : The impact of intracellular spatial organization beyond classical compartments on processes such as cell signaling is increasingly recognized. A quantitative, mechanistic understanding of cellular systems therefore needs to account for different scales in at least three coordinates: time, molecular abundances, and space. Mechanistic mathematical models may span all these scales, but corresponding multi-scale models need to resolve mechanistic details on small scales while maintaining computational tractability for larger ones. This typically results in models that combine different levels of description: from a microscopic representation of chemical reactions up to continuum dynamics in space and time. We highlight recent progress in bridging these model classes and outline current challenges in multi-scale models such as active transport and dynamic geometries.